Transmission-Blocking Strategies for Malaria Eradication: Recent Advances in Small-Molecule Drug Development - Federico Appetecchia; Emanuele Fabbrizi; Francesco Fiorentino; Sara Consalvi; Mariangela Biava; Giovanna Poce; Dante Rotili (MDPI AG, 2024)
Malaria drug research and development efforts have resurged in the last decade following the decelerating rate of mortality and malaria cases in endemic regions. The inefficiency of malaria interventions is largely driven by the spreading resistance of the Plasmodium falciparum parasite to current drug regimens and that of the malaria vector, the Anopheles mosquito, to insecticides. In response to the new eradication agenda, drugs that act by breaking the malaria transmission cycle (transmission-blocking drugs), which has been recognized as an important and additional target for intervention, are being developed. These drugs take advantage of the susceptibility of Plasmodium during population bottlenecks before transmission (gametocytes) and in the mosquito vector (gametes, zygotes, ookinetes, oocysts, sporozoites). To date, compounds targeting stage V gametocytes predominate in the chemical library of transmission-blocking drugs, and some of them have entered clinical trials. The targeting of Plasmodium mosquito stages has recently renewed interest in the development of innovative malaria control tools, which hold promise for the application of compounds effective at these stages. In this review, we highlight the major achievements and provide an update on the research of transmission-blocking drugs, with a particular focus on their chemical scaffolds, antiplasmodial activity, and transmission-blocking potential.